(untitled) - Prof. Dr. jur. Bijan Fateh-Moghadam; Prof. Dr. Hans Christoph Grigoleit; Prof. Dr. Thomas Gutmann; Prof. Dr. Katrin Höffler; Prof. Dr. Stefan Huster; Prof. Dr. Jens Kersten; Prof. Dr. Susanne Lepsius; Prof. Dr. Isabelle Ley; Prof. Dr. Matthias Mahlmann; Prof. Dr. Frank Neubacher, M.A.; Prof. Dr. Thomas Pfeiffer; Prof. Dr. Anne Sanders, M.Jur. (Oxford); et al. (RW Rechtswissenschaft, 2023)
Rechtswissenschaft is an interdisciplinary academic journal that focuses on the relations between the respective juridical fields. The journal creates an antipole to the growing specialization in academics and provides readers with an overview of the legal state of research. Thus it encourages legal discourse. Website: www.rechtswissenschaft.nomos.de